Magnetc Gradient Temperature and Geochemistry Survie S Within Pasema air Keruh Geothermal Area Empat Lawang District, South Sumatera Province Indonesia - F., Virgo; Wahyudi, .; Suharno, .; A., Zainudin; Wiwit, Suryanto (UGM, 2012)
The Pasema Air Keruh geothermal area situated within the Empat Lawang District, Sumatera Selatan Province. Magnetic, gradient temperature and geochemistry survies conducted within that area, in 9 June 2012. The magnetic and the gradient temperature were not analysed zet. The geochemical analysis using the geothermometer and geoindikator, doe to determine the reservoir characteristic and temperature. The fir-st geothermal exploration activities in Empat Lawang District Sumatera Selatan Province were carried out in the Penantian hot spring field Air Keruh Sub District and Airklinsar hot spring field Ulu Musi Sub District. The discharge test measurements show that chemical composition of the reservoir water was analyzed by standard methods and subsequently classified using Cl-S04, HC03 triangular diagram. A Na-K-Mg triangular diagram was used to classify waters according to the state of equilibrium at given temperatures. The geothermal waters are of chloride water type and from a relatively old hydrothermal system. Thermal fluid is in equilibrium with reservoir rocks. The chemical geothermometers were used to predict subsurface temperature. The calculated temperatures using Na-K geothermometers and Na-K-Mg geoindikcator is more than 300°C. However, compare with measured temperature furthere.